Role of Ethical Orientation of HRM in Establishing an Ethical Organizational Culture: A Literature Review and Implications - De Silva, N.G.V.A.; Opatha, H.H.D.N.P. (Faculty of Management Studies and Commerce, University of Sri Jayewardenepura, 2015)
Growing unethical behavior of employees in business organizations and its negative impact on the organization, economy-and the society has become a global concern over the past two decades. Hence Growing unethical behavior of employees in business organizations and its negative impact on the organization, making employees more ethical to create an ethical organizational context and its positive impact on the organization, economy and society have received growing scholarly attention in the business and organizational ethics literature. Creating and sustaining an Ethical Organizational Culture CEOC) is a crucial strategic goal for any business organization. Despite its significance in the present corporate environment, empirical investigations on EOC and the contribution of Human Resource Management (HRM) in creating and sustaining an EOC are limited. This paper reviews relevant theoretical and empirical findings of research work in literature from Business Ethics, HR, management, and organization studies fields, in the link EOC and HRM over the past three decades. The main objective of the study is to explore the role of Ethical Orientation of HRM (EOHRM) in making employees more ethical, in order to create and sustain an EOC. The paper discusses this role under four key HRM dimensions: Acquire, develop, retain and motivate ethical employees, in order to create an EOC. Working definitions for the main constructs in the study, EOHRM and EOC were developed by the authors. Systematic review method recommended by Tranfield et al. (2003) with an archival method, was used for reviewing of literature. This paper has a significant utility for future research.
Keywords: Ethics; Ethical orientation of HRM; Ethical organizational culture